Crecimiento fetal y de otros componentes del utero gravido en cabras mestizas - Roncallo F., B.A.=700 1 Sanson M., C.H.; Borela E., C.J.; .; Texeira R., M.
(Es, En)
ilus., 9 ref.
Keywords: CABRAS; GESTACION; PESO CORPORAL; FETO; UTERO; COLOMBIA